The Russian Background in George Sand’s Novel L’Homme de Neige - Anna V. Popova (Studia Litterarum)
The article presents results obtained after a thorough research of the ways of interpreting the “Russian theme” by George Sand, which has not yet become the subject of a separate study. The writer’s works for a wide range of readers objectify ethno-stereotypes related to the geographical remoteness of Russia, its climate, state structure, and national character. Based on Sand’s novel, L'Homme de Neige (1859), the article shows how the Russian theme fits into the context of her worldview and develops in accordance with her idiostyle, in which binary oppositions play a crucial role. Russian characters in the novel have no independent value but act as antipodes for good ones, whose life position is consonant with the writer’s ideas. The opposition of patriotism, authenticity, sincerity, honesty, and selflessness to corruption, imitation, hypocrisy, cunning, and mercenariness, attributed by the author to Russians or those who sympathise with them, reveals and clarifies one of the most significant categorical oppositions in George Sand’s novels structure — “natural / artificial.” The image of Russia and Russians in the writer’s works appears as a background. It is shaped by stereotypes that have already been fixed in the consciousness and are easily recognisable to the French reader, which turns out to be consonant with her negativist perception of Russian history, foreign policy, and state ideals.